Ideas: A tale of two futures - Sandrine Cathelat; Mathilde Hervieu (The UNESCO Courier, 2019)
Is artificial intelligence (AI) on the verge of becoming completely autonomous? The answer will depend on us alone. It is up to us to define the future of humanity, in harmony with this technological tool that we sometimes perceive as a terrifying monster.